1991
DOI: 10.1152/ajpcell.1991.261.6.c964
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of homogeneously small keratinocytes from newborn rat skin: possible epidermal stem cells

Abstract: The aims of the present study were to characterize the phenotype, growth kinetics, and proliferative activation in culture of a population of poorly differentiated homogeneously small (HS) keratinocytes. These slow-cycling cells were separated by unit gravity sedimentation from a population of actively proliferating basal keratinocytes in newborn rat skin. This population (approximately 1% of the total basal keratinocytes) consisted of extremely small cells with little cytoplasm or RNA. Their positive KL4 stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Culture conditions may favor proliferation of TACs and/or reprogram proliferative ability [for review see (Cotsarelis, 2006)] or in vitro analysis may reflect a wounding response, not homeostasis (Kaur, 2006). These results are consistent with the belief that stem cells have minimal clonogenic ability in vitro and that not all colony forming cells constitute stem cells (Pavlovitch et al, 1991; Budak et al, 2005; Li et al, 1998; Selver et al, 2011; Strachan et al, 2008; Schofield, 1978; Loutit et al, 1981; Louis et al, 2008). …”
Section: Discussionsupporting
confidence: 89%
“…Culture conditions may favor proliferation of TACs and/or reprogram proliferative ability [for review see (Cotsarelis, 2006)] or in vitro analysis may reflect a wounding response, not homeostasis (Kaur, 2006). These results are consistent with the belief that stem cells have minimal clonogenic ability in vitro and that not all colony forming cells constitute stem cells (Pavlovitch et al, 1991; Budak et al, 2005; Li et al, 1998; Selver et al, 2011; Strachan et al, 2008; Schofield, 1978; Loutit et al, 1981; Louis et al, 2008). …”
Section: Discussionsupporting
confidence: 89%
“…These functional features notwithstanding, our SP cells displayed a low (~3%) CFE. A literature search, though, revealed that stem cell-rich fractions exhibiting substantially lower CFEs than the source whole populations have been observed in adult rat epidermis (Pavlovitch et al, 1991) and in neonatal human foreskin (Li et al, 1998). This is remarkable considering that whole populations include a large proportion of suprabasal, differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Slow or infrequent cycling, is one of the most unique features of adult stem cells (Leblond, 1964;Bickenbach, 1981;Cotsarelis et al, 1989;Pavlovitch et al, 1991;Morris and Potten, 1994;Wei et al, 1995;Fortunel et al, 1998;Lehrer et al, 1998;Braun et al, 2003;Tumbar et al, 2004). Accordingly, we performed experiments aimed at identifying slow-and fast-cycling cells in the conjunctival and limbal epithelia and in their respective flow cytometry cohorts.…”
Section: Abcg2 Is Expressed In the Ocular Surface Epithelia In Discrementioning
confidence: 99%
“…Nevertheless an important study demonstrated that LRC isolated from mouse skin do have higher colony-forming potential in vitro than pulse-labelled cells from the same animal (Morris and Potten, 1996). In the rat it is possible not only to generate LRC but also to culture primary keratinocytes with high colony-forming efficiency and these studies also suggest that LRC are clonogenic in vitro (Pavlovitch et al, 1991;Kobayashi et al, 1993).…”
Section: Label Retention In Comparison With Other Stem Cell Charactermentioning
confidence: 99%